Higher mass meningococcal group C-tetanus toxoid vaccines conjugated with carbodiimide correlate with greater immunogenicity. Issue 13 (17th March 2020) - Lockyer, Kay; Gao, Fang; Francis, Robert J.; Eastwood, David; Khatri, Bhagwati; Stebbings, Richard; Derrick, Jeremy P.; Bolgiano, Barbara
Highlights: A panel of MenC-TT conjugate vaccines was produced with different chain-lengths; MenC conjugates with longer saccharide chains were more immunogenic in mouse study; Stoichiometric modelling of glycoconjugates can elucidate higher order structures; Larger sized conjugates stimulated higher level of splenocyte profileration; Confocal microscopy can be used to image meningococcal C on splenocyte surface. Abstract: To examine the link between meningococcal C (MenC) vaccine size and immunogenic response, a panel of MenC glycoconjugate vaccines were prepared differing in chain length, molar mass and hydrodynamic volume. The preparations consisted of different lengths of MenC polysaccharide (PS) covalently linked to monomeric purified tetanus toxoid (TT) carrier protein using the coupling reagent ethylcarbodiimide hydrochloride (EDC). Size exclusion chromatography with multi-angle light scattering (SEC-MALS) and viscometry analysis confirmed that the panel of MenC-TT conjugates spanned masses of 191, 500 to 2, 348, 000 g/mol, and hydrodynamic radii ranging from 12.1 to 47.9 nm. The two largest conjugates were elliptical in shape, whereas the two smallest conjugates were more spherical. The larger conjugates appeared to fit a model described by multiple TTs with cross-linked PS, typical of lattice-like networks described previously for TT conjugates, while the smaller conjugates were found to fit a monomeric or dimeric TT configuration. The effect of vaccine conjugate size on immune responses was determined using a two-dose murine immunization. The two larger panel vaccine conjugates produced higher anti-MenC IgG1 and IgG2b titres after the second dose. Larger vaccine conjugate size also stimulated greater T-cell proliferative responses in an in vitro recall assay, although cytokines indicative of a T-helper response were not measurable. In conclusion, larger MenC-TT conjugates up to 2, 348, 000 g/mol produced by EDC chemistry correlate with greater humoral and cellular murine immune responses. These observations suggest that conjugate size can be an important modulator of immune response.